2022
DOI: 10.1155/2022/1972389
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Badminton Player’s Step Training Model Based on Big Data and IoT Networks

Abstract: In view of the poor effect of badminton players’ physical fitness and response training, this paper puts forward the construction method of badminton players’ pace training model based on big data, constructs badminton players’ pace training index by combining big data technology, optimizes the pace training evaluation algorithm, and puts forward the corresponding Badminton Players’ pace training method to achieve the model design goal. Finally, experiments show that the badminton athlete’s pace training model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Based on the results of the factor analysis of the structure of the readiness of basketball students of humanitarian universities and the generalization of literature data [9,10,13,14], a training methodology for athletes, players of the humanitarian university basketball team was developed, which formed the basis of a formative pedagogical experiment.…”
Section: Intervention Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of the factor analysis of the structure of the readiness of basketball students of humanitarian universities and the generalization of literature data [9,10,13,14], a training methodology for athletes, players of the humanitarian university basketball team was developed, which formed the basis of a formative pedagogical experiment.…”
Section: Intervention Technologymentioning
confidence: 99%
“…This opinion is based on the theory of I.P. Pavlov [9,10] about the existence of different types of thinking in people and on the data of modern scientists, who showed that artistic thinking is more common among students of humanitarian specialties.…”
Section: Intervention Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Step Training Model Based on Big Data and IoT Networks" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Security and Communication Network Has Retracted The Article...mentioning
confidence: 99%